2021
DOI: 10.3389/fpls.2021.660224
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of Humic Acids Extracted From Shale Ore: Molecular Characterization and Structure-Activity Relationship With Tomato Plant Yield Under Nutritional Stress

Abstract: The increasing demands for biostimulants in the agricultural market over the last years have posed the problem of regulating this product category by requiring the industry to make available the information about efficacy and safety, including the explanation of mode of action and the definition of bioactive constituents. In the present study, we tested the biostimulant proprieties of a sedimentary shale ore-extracted humic acid (HA) on Micro Tom tomato plants under increasing nutritional stress and investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 104 publications
(111 reference statements)
2
12
0
2
Order By: Relevance
“…A three-year investigation by Suman and collaborators [209] found that adding 0.5 L humic acid ha −1 via fertigation to open-field-grown tomato plants did not enhance growth and yield when fertilization was 100% of the recommended dosage, which is also consistent with what Monda and collaborators [211] recently found. When fertilization was 80% of the recommended dosage, it performed significantly better than its untreated control (12.6% higher yielding), and statistically equal to the 100% fertilization group; the same results were also recorded when 25 and 50 mg of HAs were added to a full-strength nutrient solution [212], which may point to differences in either the plant, the experimental setup, and/or the HA source material and dosage.…”
Section: Implication Of Biostimulant Substance Treatments On Nightshade Green Growth and Fruit Yieldsupporting
confidence: 80%
“…A three-year investigation by Suman and collaborators [209] found that adding 0.5 L humic acid ha −1 via fertigation to open-field-grown tomato plants did not enhance growth and yield when fertilization was 100% of the recommended dosage, which is also consistent with what Monda and collaborators [211] recently found. When fertilization was 80% of the recommended dosage, it performed significantly better than its untreated control (12.6% higher yielding), and statistically equal to the 100% fertilization group; the same results were also recorded when 25 and 50 mg of HAs were added to a full-strength nutrient solution [212], which may point to differences in either the plant, the experimental setup, and/or the HA source material and dosage.…”
Section: Implication Of Biostimulant Substance Treatments On Nightshade Green Growth and Fruit Yieldsupporting
confidence: 80%
“…In addition, HS also up-regulate the genes responsible for production of transport proteins responsible for NO 3 – ( Quaggiotti et al, 2004 ), HPO 4 – ( Jindo et al, 2016 ) and Fe ( Trevisan et al, 2010 ) uptake into root cells. Collectively, up-regulation of these types of proteins can result in increased nutrient use efficiency of N, P, and Fe, particularly in stressed plants ( Monda et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) was used to differentiate the molecular signature of humic acids from different sources. The degree of humification, determined according to aromaticity and degree of saturation, increases the HA from soil, river, and leonardite/oxidized lignite [ 179 ]. FT-ICR MS, in combination with 13 C-CPMAS NMR spectroscopy and FT-IR ATR, revealed the co-existence of anti-oxidant and pro-oxidant moieties and properties of humic acid extracted from lignite [ 180 ].…”
Section: Humic Substances As Microalgae Biostimulantsmentioning
confidence: 99%